Biomimicry and aerodynamic performance of multi-flapping wing drones - Billingsley, Ethan; Ghommem, Mehdi; Vasconcellos, Rui [UNESP]; Abdelkefi, Abdessattar; AIAA (Amer Inst Aeronautics & Astronautics, 2021)
Certain birds have been noted to fly in V-formation, an arrangement which may be used to conserve energy when migrating over long distances without stopping and feeding. The use of such grouping arrangement and organized pattern has been observed to enable longer endurance and less power consumption in comparison with single flights. Based on this observation, a multiple-flapping-wing air vehicle that is designed to exploit the aerodynamic benefit of this type of flight is proposed. In addition, focus is placed on both long-range flight capability for use in search-and-rescue operations and biomimicry for use in reconnaissance applications. To accomplish this goal, an aerodynamic analysis is carried out for several different wing shapes using the unsteady vortex lattice method to identify the optimal formation angle for a 3-member group size of flapping wings in V-formation that maximizes the aerodynamic loads under several constraints. The simulation results reveal that an albatross-inspired wing shape is the optimal configuration for producing lift, while the rectangular wing shape is the optimal choice for producing thrust.